Kinematic analysis of shot-putting performed by wheelchair athletes of different medical classes - Chow, J. W.; Chae, W. S.; Crawford, M. J. (Journal of Sports Sciences, 2000)
The aim of this study was to identify those kinematic characteristics that are most closely related to an athlete's medical classification and measured distance of a put. Two S-VHS camcorders (60 fields per second) were used to record the performance of 17 males of different classes. Each participant performed six trials and the best trial for each was selected for analysis. Three-dimensional kinematics of the shot and upper body segments at the instant of release and during the forward thrust (delivery) were determined. The average speeds and angles of the shot at release for different classes (5.3-7.8 ms-1 and 21.2 to 34.4°, respectively) were smaller than those exhibited by elite male able-bodied throwers. The height of the shot at release, the angular speed of the upper arm at release, the range of motion of the shoulder girdle during the delivery, and the average angular speeds of the trunk, shoulder girdle and upper arm during the delivery, were all significantly correlated with both the classification and measured distance (P < 0.05). The results indicate the importance of achieving a high average angular speed for each upper body segment during the delivery.